PENGARUH STATUS GIZI TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK 5-6 TAHUN DI TK MUJAHIDIN - Prameswari, Dewi Ariesta; Yuniarni, Desni; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThis study aims to determine the effect of nutritional status on gross motor development in children aged 5-6 years in TK Mujahidin II Kecamatan Pontianak Timur Year 2017. This study used cross sectional survey method. The study was conducted at TK Mujahidin II, Pontianak Timur sub-district on 20 to 24 November 2017. Samples are children aged 5-6 years as many as 60 children from the population of 60 children. This research uses saturation sampling technique that is sampling which all member of population used as sample. Data source uses primary data and secondary data. Data collection techniques use observation and documentation. Data analysis technique using simple linear regression test, t test, kolmogorov smirnov data normality test, regression coefficient test. The results showed the regression coefficient between nutritional status to motor development of -.249. Hypothesis testing, obtained t count equal to -2.020 bigger than t table equal to 2,002. This means that there is a negative and significant influence between nutritional status and gross motor development. So it can be concluded that there is a negative and significant influence between nutritional status with Â gross motor development of children aged 5-6 years in TK Mujahidin II Kecamatan Pontianak Timur.Keywords: Nutritional Status, Gross Motor Development